Relación entre la hormona antimülleriana y la reserva ovárica en vacas donadoras Brahman y Blanco Orejinegro - Riveros Pinilla, Diego A. (2022)
The aim of this study was to compare the levels of anti-Müllerian hormone (AMH) in female Brahman and Blanco Orejinegro oocyte donors and its relationship with ovarian reserve and embryo production in vitro. Oocytes were obtained from 42 Brahman and 38 Blanco Orejinegro females by ultrasound-guided ovarian puncture (OPU). Blood samples were collected prior to OPU for determination of serum AMH concentrations. The oocytes and embryos were cultured individually for each donor. The results showed that serum AMH concentrations were 0.78 ± 0.34 ng/ml (0.09-1.89 ng/ml) for Brahman cows and 0.72 ± 0.32 ng/ml (0.13-1.19 ng/ml) for Blanco Orejinegro cows. The correlation between the concentration of AMH and the number of follicles was r=0.77 and r=0.74 for the Brahman and Blanco Orejinegro cows, respectively, as well as a positive correlation between the concentration of AMH and the number of blastocysts (r=0.55 and r=0.6, respectively). It is concluded that the Brahman donors have a higher concentration of AMH and a greater ovarian reserve than the Blanco Orejinegro donors; however, a higher correlation was found between the concentration of AMH and the number of blastocysts in Blanco Orejinegro donors than in Brahman.